2014
DOI: 10.1142/s1088424614500710
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of chlorophylls in photosynthetic proteins: from the viewpoint of coordination chemistry

Abstract: We conducted a meta-analysis of (bacterio)chlorophyll [(B)Chl] molecules in photosynthetic pigment-protein complexes from the viewpoint of coordination chemistry. We surveyed the ligand species and site in the axial coordination of 146 Chl and 21 BChl molecules in 42 reported crystal structures of 12-type proteins. The imidazolyl moiety of histidine (His) is the most abundant ligand, and the second is water, a much weaker ligand. We focused on the positions, the circumstances, and the macrocycle sides for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 60 publications
0
21
0
Order By: Relevance
“…It has been reported that the a-ligated coordination of chlorophyllsi sp referred to the b-ligation in variousp hotosynthetic proteins. [36][37][38] Our molecular modeling study by molecular mechanics (MM +)a nd semi-empirical molecular orbitalc alculations (PM3) showedt hat the a/a-coordination dimer structure ( Figure 9) was the most energeticallys table (Figures S25-S33 and Ta ble S2).…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that the a-ligated coordination of chlorophyllsi sp referred to the b-ligation in variousp hotosynthetic proteins. [36][37][38] Our molecular modeling study by molecular mechanics (MM +)a nd semi-empirical molecular orbitalc alculations (PM3) showedt hat the a/a-coordination dimer structure ( Figure 9) was the most energeticallys table (Figures S25-S33 and Ta ble S2).…”
Section: Resultsmentioning
confidence: 97%
“…[1][2][3] LH antennas contain severalp igments, including chlorophylls (Chls), bacteriochlorophylls (BChls), bilins, and carotenoids. [4] X-ray analysis of crystal structures of several LH antennasindicated that the pigments are located in specific arrays by binding with peptides: [5] photosystem (PS) 1, [6] PS1light harvesting complex (LHC) 1s upercomplex, [7] PS2, [8] LHC2, [9] peridinin chlorophyll protein, [10] LH1-RC, [11] LH2, [12] and Fenna-Matthews-Olson protein. [13] Chlorosomes are one of the unique LH antenna apparatuseso fg reen photosynthetic bac-teria and have attracted much attention from the viewpoints of supramolecular structures and photophysicalp roperties.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrated excitation energy is utilized for electron transfer between chlorophyll pigments in a reaction center. These ultrafast photoinduced processes with high efficiency are performed in pigment-peptide complexes 6 or pigment self-aggregates. 7 Chlorophylls-a, -b, -c, -d, and -f are recognized as photosynthetically active pigments in oxygenic phototrophs, while bacteriochlorophylls-a, -b, -c, -d, -e, -f, and -g function in anoxygenic photosynthetic bacteria ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%